Long-term elevated LDH values preceding heart failure in an elderly patient; a dilemma in the differential diagnosis (Bangladesh Journal of Medical Science, 2026)
Although LDH is one of the markers that can be significantly elevated in patients with tumors, it can also be elevated in patients with inflammation, anemia, tuberculosis, as well as myocardial infarction. Bearing in mind that elevated LDH indicates tissue damage here we monitor the LDH enzyme over time in a 78-yearold patient who previously had rheumatoid arthritis, a heart rhythm disorder with an implanted pacemaker, anemia and weight loss. Elevated LDH values were the reason for a detailed examination, in which the existence of hematological malignancy, lung and digestive system tumors, changes in the kidneys function and hemolysis were excluded. However, during heart rhythm disturbances with disease progression, there was a significant increase in NT pro-BMP (10-11 times from range values, LDH also increased slightly (range 3-5 times) but without a significant increase in troponin or CRP. After cardiology treatment and by adjusting the work of the Pacemaker and with the normalization of the heart rhythm, there is a normalization of NT pro-BMP and LDH values. We conclude that LDH beside NT pro- BMP can also be a useful marker that indicates heart weakness even before the appearance of clinical symptoms, and we recommend it in clinical work.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 1001-1007